The impact of COVID-19 on recovery in Henoch-Schönlein purpura patients: a cross-sectional questionnaire study during a distinctive period - Jin, Lihua; Zhao, Caixia; Xiong, Jiao; Chang, Qiqi; Su, Yan; Dou, Binjing; Zhang, Li; He, Ping (Frontiers in Pediatrics, 2026)
BackgroundThe rising incidence of infectious diseases underscores the necessity for vaccination such as COVID-19. Beyond examining the side effects in healthy individuals, it is crucial to investigate the vaccination experiences of vulnerable populations, particularly those with Henoch-Schönlein purpura (HSP).MethodsA questionnaire study was conducted during the period of rapid outbreak following the relaxation of travel restrictions in China towards the latter stages of the COVID-19 pandemic.ResultsDespite non-HSP individuals exhibiting more pronounced symptoms of cough, fatigue, dizziness, and headache compared to HSP patients, the HSP group displayed significantly lower rates of vaccination post-matching. Specifically, only 63% of HSP individuals completed the full vaccination regimen, with no significant association found between vaccination status and improved recovery or mitigation of HSP symptoms. Among HSP individuals, only improvement in diarrhea symptoms was positively correlated with recovery time, while fully vaccinated HSP children exhibited more abnormal symptoms during the recovery period.ConclusionResults from this study on COVID-19 vaccination status among pediatric patients who required hospital visits during the peak of the pandemic indicated that vaccination rates were comparatively lower among patients with HSP, even amidst severe outbreaks. HSP patients who completed the full vaccination regimen appeared to experience more pronounced adverse symptoms. This observation suggests that their increased vaccine hesitancy relative to the general population may be justified and warrants careful consideration.